Critical evaluation and comparison of nutritional clinical practice guidelines for cancer patients. Issue 5 (May 2023) - Bakaloudi, Dimitra Rafailia; Papaemmanouil, Androniki; Vadarlis, Andreas; Makrakis, Dimitrios; Germanidis, Georgios; Timotheadou, Eleni; Chourdakis, Michail
Summary: Background: The growing incidence of cancer globally, and the importance of nutrition support for these patients, emphasize the need for the development of nutritional clinical practice guidelines and consensus papers (CPGs) in the field. Numerous relevant CPGs have been published by several organizations worldwide. The aim of this systematic review was to compare the content of the existing CPGs and evaluate the quality of their development using the AGREE-II tool. Methods: A systematic literature search in PubMed, Embase and Web of Science databases was conducted for the identification of relevant CPGs and consensus papers. Eligible CPGs was blindly evaluated by four appraisers according to the Appraisal of Guidelines for Research and Evaluation ΙΙ (AGREE-II) tool. Results: In total 15 CPGs were identified and were evaluated. All but one set of CPGs underlined the importance of nutritional screening and assessment, whereas recommendations on nutritional interventions, supplements, management of complications and nutritional follow-up were also reported by several organizations. AGREE-II results showed that two CPGs were characterized as high, eight as moderate and five as low regarding their quality of development. Conclusions: Variety on recommendations could be observed between CPGs that should be considered when applied into clinical practice. Limitations of the existing CPGs could be the fact that they are non-specific and only a minority of them are focused to specific cancer types. Frequent updates for CPGs and inclusion of more nutritional topics should be considered for some CPGs. Improvement of the quality of the CPGs development should also be pursued in future.